Discovery of buried historical structures in the Kaveri–Kollidam interfluve, southern India - Ramkumar, M.; Kumaraswamy, K.; Balasubramani, K.; Abdul Rahaman, S.; Jegankumar, R.; Kumara Ganesh, U.; Manikandan, E.; Balasundareshwaran, A.; Prithiviraj, G.; Ayyanthurai, R.; Santosh, M.; Ramasamy, Nagarajan; et al. (2018)
The Srirangam interfluve, formed between the Kaveri and Kollidam Rivers in southern India, has been a religious and cultural human settlement for over 2000 years of recorded history. It contains thousands of ancient, yet in use, man-made structures. Owing to its geographic location, and episodic catastrophic floods from the Kaveri and Kollidam Rivers, the region has been inundated frequently leading to the burial of many smaller structures. Thematic maps of geomorphology, vegetation index, land use, digital elevation model, slope, etc., have been generated through multi-temporal remote sensing satellite images. A compilation of historic (stone inscriptions, temple documents) and literature data followed by detailed survey of the region using vertical electrical sounding (VES) and ground-penetrating radar (GPR) through 200 and 400 MHz shielded antennas has led to the discovery of several buried manmade structures at various depths ranging from 0.54 to 3.55 m below ground level (b.g.l.) that were known only in the literature, hearsay and folklore. The VES, GPR and field surveys delineated four major soil/sediment horizons below the ground surface. Sedimentological characteristics of a massive river sand bed found overlying a weathered zone suggest deposition during a major catastrophic flood. The occurrence of flood deposits burying historic structures especially adjoining the regional tectonic structure indicate episodically active climatic and tectonic processes that played a significant role in the burial of ancient-historic land surface and manmade structures that were under desolation after invasion and desecration by war-lords of yore. This study demonstrates the potential of combining traditional knowledge and modern technologies to gain insights to locate historic/archaeological sites and discover buried structures.